The mind of the strategist the art of Japanese business - Ōmae, Kenʾichi. (New York Mcgraw-Hill, 1982)
A Masterful Analysis of Company, Customer, and Competition Kenichi Ohmae - voted by The Economist as "one of the world's top five management gurus" - changed the landscape of management strategy in "The Mind of the Strategist". In this compelling account of global business domination, Ohmae reveals the vital thinking processes and planning techniques of prominent companies, showing why they work, and how any company can benefit from them. Filled with case studies of strategic thinking in action, Ohmae's classic work inspires today's managers to excel to new heights of bold, imaginative thinking and solutions. "In many ways, Ohmae can be considered the modern reincarnation of a much older guru, Adam Smith." -"Journal of Marketing". "A fascinating window into the mind of one of Japan's premier strategists...full of ideas about how to improve strategic thinking."- Michael E. Porter, Graduate School of Business Administration, Harvard University
Includes index.
Keywords: Industrial management